2019
DOI: 10.1111/jre.12650
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of spreading vasodilation in the human gingiva evoked by nitric oxide

Abstract: Background and Objective Spreading vasodilation is an important means of increasing local blood flow effectively during increased metabolic demands or in case of vascular injury. Our aim was to develop a technique proving the presence of spreading vasodilation in the human keratinized gingiva. Methods Local vasodilation was evoked by the application of nitric oxide (NO) donor nitroglycerin into a well, fixed 2 mm above the marginal gingiva, in 20 subjects with healthy periodontal tissue. Either 1 or 8 mg/mL ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The sample size was determined by experience from the previous study with very similar set-up [ 34 ]. Data are presented in the text and the figures as mean ± standard error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was determined by experience from the previous study with very similar set-up [ 34 ]. Data are presented in the text and the figures as mean ± standard error.…”
Section: Discussionmentioning
confidence: 99%
“…GBF changes were continuously recorded for further 14 min by LSCI (PeriCam PSI HR System, Perimed AB, Stockholm, Sweden) with a 2 × 3 cm measurement area, 0.06 mm/pixel resolution and 2 images/sec. The gingival thickness was measured by PIROP ultrasonic biometer (Echo-Son, Puławy, Poland) [ 34 , 35 ] at the test and control sides according to the location of the 5–5 ROIs in group A, and at the midway1 and apical regions in group B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vasodilation should ascend (i.e., spread) to the proximal feed artery and arterioles to ensure the blood supply of the distal microcirculatory network [ 1 ]. Recently, spreading vasodilation and vasoconstriction evoked by nitric oxide or epinephrine was observed in human gingiva [ 2 , 3 ], which could have an impact on flap survival and the spatial progression of periodontitis. However, some evidence suggests that microcirculation of the human gingiva might be affected by sex.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, clinical observations revealed that the marginal gingiva could survive after horizontal incision and it could be revascularized by rapidly developing anastomosis from the periodontal plexus (Cutright, ; Kennedy, ). A recent observation showed that local vasodilation evoked on the keratinized gingiva spreads apically (Ganti et al, ) opening the supply vessels. This phenomenon could also have an important role in flap survival.…”
Section: Introductionmentioning
confidence: 99%